2018
DOI: 10.29333/ejgm/90278
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of anterior pituitary gland in women patients with recent fibromyalgia: A cross-sectional observational study

Abstract: Objective: To assess the basal levels of circulating anterior pituitary gland hormones in women presented with a recent diagnosis of fibromyalgia (FM). Methods: This cross-sectional study was included 130 women presented with a clinical signs and symptoms of FM women and 35 age-matched healthy subjects served as controls. The plasma levels of growth hormone (GH) and adrenocorticotrophic hormone (ACTH), and the serum levels of prolactin (PRL) and thyroid stimulating hormone (TSH) were measured. The scores of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…A study confirmed that the score of both FSS, ISI, and Hamilton's scale for depression (HSD) was significantly higher in fibromyalgia patients than the corresponding value in healthy subjects. 19 Our study confirms a significant bivariate correlation between the fatigue severity with the number of tender points, body mass index, and waist-to-height ratio. 20,21 Factors observed to affect the body mass index and central obesity are gender and ethnicity, and socioeconomic factors.…”
Section: Discussionsupporting
confidence: 85%
“…A study confirmed that the score of both FSS, ISI, and Hamilton's scale for depression (HSD) was significantly higher in fibromyalgia patients than the corresponding value in healthy subjects. 19 Our study confirms a significant bivariate correlation between the fatigue severity with the number of tender points, body mass index, and waist-to-height ratio. 20,21 Factors observed to affect the body mass index and central obesity are gender and ethnicity, and socioeconomic factors.…”
Section: Discussionsupporting
confidence: 85%
“…For example, approximately half of the studies reported decreased levels of blood cortisol 19,21,22,38,69,89 or ACTH 1,13,81,89 for individuals with FMS compared with FMS-free controls, whereas the other half reported increased levels for the respective outcome measures. 3,6,7,12,14,60 This suggests that these markers do not appear to be altered per se in FMS. This conclusion is supported by sensitivity analyses because still no differences between groups were found, even when outliers with remarkably diverging values were excluded.…”
Section: Discussionmentioning
confidence: 97%
“…In FM/CFS patients, TSH levels vary across studies. In one study in patients with FM, basal TSH serum levels were significantly higher than those in controls, 33 whereas another study demonstrated normal TSH and normal basal T3 and T4 levels. 49 Significantly higher serum TSH levels were found in CFS patients than controls, whereas the free thyroxine level of CFS patients was comparable to that of controls.…”
Section: The Hypothalamo-pituitary Thyrotropic Axismentioning
confidence: 91%
“…In FM, the PRL serum levels vary across studies. Compared to controls, lower 28 , 43 or similar 18 or slightly higher PRL levels 29 , 33 , 44 , 45 have been documented. On the other hand, aFM diagnosis was highly prevalent in patients with high PRL serum levels.…”
Section: Prolactin (Prl)mentioning
confidence: 96%